OC-074 Nutritional Optimisation And Pancreatic Enzyme Supplementation In Chronic Pancreatitis: Are We Giving Our Patient's Enough Advice?. (9th June 2014) - Paranandi, B; Patel, PS; Joshi, D; El-Sayed, GH; Koshy, K; Ghai, A; Chapman, MH; Pereira, SP; Webster, GJ; Johnson, GJ
Abstract : Introduction: There is a significant risk of malnutrition in patients with Chronic Pancreatitis (CP) with evidence to suggest that good dietary counselling for a balanced homemade diet is as good as commercial food supplements to improve nutrition. Pancreatic enzyme replacement therapy (PERT) is associated with improved absorption of nutrients as well as relief of GI symptoms. Proton pump inhibitors (PPI) improve the bioavailability and efficacy of PERT. Data regarding PERT compliance and education is lacking. We aim to determine the prevalence of exocrine insufficiency and compliance to PERT in patients with CP. Methods: Prospective study of consecutive patients with CP attending a tertiary clinic between October and December 2013. They were invited to participate in a face-to-face questionnaire study. Faecal elastase (FE) results were collated and the Malnutrition Universal Screening Tool (MUST) score was calculated. Results: A cohort of 86 patients identified were predominantly male (67%), White British (62%), median age 58 years (range 18–90), of socio-economic class (SEC) 8 (21% never worked/long-term unemployed) with educational level (EL) 1 (29% degree or equivalent). Aetiologies included alcohol (29%), idiopathic (25%), autoimmune (22%) and gallstones (11%). Median follow up was 27.5 months (range 0–151) from index appointment. 69 patients underwent routine measurement for FE, 61% (42/69) of whom were deficient (<200 µg/g) and 49% (34/69) severely deficient (<100 µg/g) suggesting exocrine insufficiency of the pancreas. 60% (25/42) of patients with confirmed exocrine insufficiency had active prescriptions for PERT, however only 40% (17/42) had PPI co-prescribed. Compliance and correct administration of PERT was observed in 56% (14/25) of patients. In those who were non-compliant or incorrectly administering PERT, nil patients (0/11) had undergone dietitian review within the previous 12 months and more than 50% (6/11) of these patients had MUST score ≥1 (conferring medium to high risk of malnutrition). Conclusion: Exocrine insufficiency is under-recognised in patients with CP and compliance with PERT is poor. Our data shows that the majority of patients who are not compliant with PERT are at medium to high risk of malnutrition. This highlights the need for structured dietetic involvement in the management of patients with CP in the clinic environment including biochemical testing of exocrine function, education about the natural history of CP, PERT administration and concomitant acid suppression. Disclosure of Interest: None Declared.